Análise do comportamento de secagem do óxido de ferro em estufa - Macedo, Luís Felipe de (Universidade Federal de São Carlos, 2025)
The present Final Course Project, entitled “Drying Behavior Analysis of Iron Oxide in an Oven”, proposes the study and characterization of the drying process of two important inorganic pigments widely used in industry: yellow iron oxide (Goethite, α-FeOOH) and black iron oxide (Magnetite, Fe3O4). The drying stage is a fundamental unit operation in the manufacture of pigments, exerting direct influence on the properties of the final product, such as crystallinity, particle size, and tinting strength. The main objective of this work was to analyze the variation of moisture content and the drying rate of samples of these materials in an oven under controlled temperature conditions, aiming to obtain empirical data to optimize energy efficiency and processing time. Gravimetric tests were conducted at temperatures of 100 °C, 110 °C, and120 °C. The theoretical foundations indicate that the structural differences between Goethite, an oxyhydroxide with high affinity for water, and Magnetite, an anhydrous oxide with a compact structure, are determining factors for their kinetic behavior. The experimental results confirmed that Goethite exhibited higher moisture retention and a longer drying time, with kinetics predominantly in the falling-rate period, limited by internal diffusion of bound moisture. Magnetite, on the other hand, demonstrated a significantly faster drying process. Increasing the temperature from 100 °C to120 °C resulted in a reduction of the total drying time for both samples. It was concluded that the drying process of Magnetite is more favorable in terms of speed and potentially energy consumption, providing important comparative results that serve as a reliable starting point for the analysis and further investigation of the materials in question.
Analysis of the drying behavior of iron oxide in an oven
Keywords: Secagem; Óxido de Ferro; Drying; Iron oxide; ENGENHARIAS::ENGENHARIA QUIMICA::OPERACOES INDUSTRIAIS E EQUIPAMENTOS PARA ENGENHARIA QUIMICA; 9. Indústria, Inovação e Infraestrutura